Diogenes Syndrome: a late-onset case in frontotemporal dementia - L.P. Ferreira; S. Gomes-da-Costa; N. Santos; A. Alho; R. Gasparinho; M. Martins (Psicosomática y Psiquiatría, 2021)
Diogenes Syndrome (DS) is a behavioural disorder characterized by severe self-neglect. In addition, DS is characterized by domestic squalor, social withdrawal, syllogomania and refusal of help that may be precipitated by stressful events. Primary DS reports are rarely described. Secondary DS is related to mental disorders. The time span in which the syndrome develops is undefined, though it is most accurately characterized as a reaction to stress that occurs late in life. This specific behavioural disorder referred to as DS is a significant functional problem contributing to increased morbidity and mortality and may be due to one or several underlying mecha- nisms, including personality disorder and frontotemporal dementia. We describe a case of DS in a 90-year-old man which presented with a 5- year history of personality changes, progressive beha- vioural changes and decline in memory. Neuropsychological testing found executive deficits, decreased verbal fluency and disturbed memory. CT-Scan imaging revealed cerebral atrophy possibly more prominent in the frontotemporal regions. His hoarding, compulsive and collecting behaviours decreased with sertraline, donepezil and risperidone. DS is a severe psychiatric condition with a multifactorial aetiology. It is strongly related to functional and cognitive decline, specially in elderly patients with comorbid frontotemporal dementia. DS represents a clinical, social and ethical challenge that requires a multidisciplinary team approach. Further investigation into the hoar- ding behaviour´s aetiology may lead to the development of treatment options for patients with frontotemporal dementia.